1995
DOI: 10.1007/bf00192113
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and clinical significance of chromogranin A and secretogranin II immunoreactivity in colorectal adenocarcinomas

Abstract: Colorectal adenocarcinomas may display features of endocrine differentiation, shown by argyrophil stains and by the expression of endocrine markers such as chromogranin A. We investigated chromogranin A and secretogranin II immunoreactivity in a series of 208 carcinomas of the large bowel to assess the prevalence and clinical significance of endocrine differentiation. Tumors expressing endocrine markers were classified as low expressors (< than 1 immunoreactive tumour cell/mm2) and high expressors (> than 1 im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…In the present series, cases having a neuroendocrine differentiated component in the primary tumors had a slightly shorter survival both from the time of diagnosis and the time from metastatic spread but statistical significance was reached for the latter case only, possible due to the relatively small sample size. Other literature data are in line with this observation [13,19,20], although some authors found no prognostic differences between neuroendocrine differentiated and conventional colorectal carcinoma [21]. No correlation was also observed with any clinical pathological parameter.…”
Section: Discussionsupporting
confidence: 80%
“…In the present series, cases having a neuroendocrine differentiated component in the primary tumors had a slightly shorter survival both from the time of diagnosis and the time from metastatic spread but statistical significance was reached for the latter case only, possible due to the relatively small sample size. Other literature data are in line with this observation [13,19,20], although some authors found no prognostic differences between neuroendocrine differentiated and conventional colorectal carcinoma [21]. No correlation was also observed with any clinical pathological parameter.…”
Section: Discussionsupporting
confidence: 80%
“…6,7,26 In our study, the majority of tumors had focal NE differentiation (<5% of tumor cells). This finding was similar to previous studies, which found focal NE differentiation in tumors from multiple organ sites, including tumors of the pancreas, 13 colon, 21,22,25,27,28 and esophagus. 7,26 It is noteworthy that, in the current study, the percentage of tumor cells with NE differentiation was increased significantly in residual tumor in posttreatment resection specimens compared with paired tumor in pretreatment biopsy specimens.…”
Section: Discussionsupporting
confidence: 81%
“…Nowadays, a common endodermal ancestor has been wellestablished for the exocrine as well as NE cells of the gastrointestinal and respiratory tracts [45,46]. NE expression is a common characteristic of tumors arising in organs normally containing NE cells [47][48][49][50]. Interestingly, NE cells of both normal and neoplastic prostate have been found to express PSA antigen [23,51].…”
Section: Discussionmentioning
confidence: 99%
“…This was first suggested by Cohen et al [19], who detected CgA expression in 50% of the tumors in their series and found a strict correlation between endocrine differentiation and an adverse prognosis. Unlike Cohen et al [19] we investigated a consecutive series of surgically removed PACs, discarding bioptic samples because of the nonhomogeneous distribution of neoplastic NE cells in nonendocrine tumors [49,50], and then dividing the IR cases into low and high NE expressors. Using this methodological approach, the NE differentiation of prostatic adenocarcinomas appears to be a quite frequent event (≈86%), that per se militates against its supposed unfavorable prognostic significance.…”
Section: Discussionmentioning
confidence: 99%